Dietary practices and nutritional profile of female nurses from Government Hospitals in Delhi, India - Shipra Gupta (Wolters Kluwer Medknow Publications, 2017)
Background: Nursing is a demanding profession and nurses face a considerable degree of stress at work that can adversely influence their dietary practices and nutritional status. The current study was designed to conduct a preliminary investigation of the dietary practices and nutritional profile of nurses from government hospitals in Delhi. Materials and Methods: A cross-sectional descriptive study was carried out among 80 female nurses aged between 25 and 39 years from government hospitals. Data on demographic profile and dietary practices were gathered using a questionnaire-cum-interview schedule. Nutrient intake of the participants was determined using a 2-day 24-hour diet recall method, and adequacy of intake of nutrients was assessed using the Nutrient Adequacy Ratio approach. Weight, height, and waist circumference were recorded and the body mass index (BMI) and waist-to-height ratio (WHtR) were computed. Results: Findings revealed that though majority of nurses were involved in rotating shift duties in their hospitals, more than two-thirds of them had more or less appropriate dietary practices. Intake of most nutrients, except iron, vitamin A, vitamin B12, dietary folate, and riboflavin ranged from fairly adequate to adequate among nearly 85% of the nurses. Approximately 70% of the nurses were categorized as overweight and obese and had a WHtR above 0.52. Conclusions: The study indicated that most female nurses in government hospitals in Delhi had appropriate dietary practices and nutrient intakes but still had high BMI and WHtR, which increased their vulnerability to health problems.